Development of a stochastic simulation model to evaluate costs of porcine cysticercosis control programmes - Gallegos, Linda (2022)
The aim of this study was to develop a stochastic simulation model to estimate implementation costs of porcine cysticercosis (CP) control programmes. Three scenarios were proposed: (1) use of a commercial recombinant vaccine (RV), (2) mixed use of RV plus oxfendazole (OFZ), and (3) dosing with OFZ. To establish the efficacy of the interventions, the probabilities of elimination of cysticercosis were obtained through the “cystiSim” agent-based model. The cost model was developed in R with 10 000 iterations. It was found that the mixed scenario offered a probability of 0.987 eliminating cysticercosis in 6.5 years and with an annual cost of S/. 335,208 (95% CI: S/ 309,922 – 368,698) (1 US$ = S/. 3.75). In contrast, the dosing strategy with OFZ proved to be less expensive with S/. 260,518 (95% CI: S/ 237,559 – 293,704) per year and a probability of elimination of 0.951 in the same evaluation period. In scenarios 1 and 2, the drug cost category is the highest, representing about 50% of the final cost, while in scenario 3, the highest cost is personnel, followed by drugs. The work concludes that the dosing strategy with OFZ is the least expensive alternative of the proposed scenarios.